Macrofinance Modeling from Asset Allocation Perspective - Kollár, Miroslav (2011)
The dissertation dealt with the interaction between the macro-economy and financial markets. In the first part of the dissertation I laid down a general case for macro-based active asset allocation. In the main part of my dissertation, after a theoretical introduction to term structure models and macrofinance models, I developed a VAR macrofinance model of the term structure of interest rates for the Czech economy based on the dynamic interpretation of the Nelson-Siegel model, and showed the use of such modeling framework in bond-yield prediction and asset allocation.